The Role of Gender in Language Use Patterns in the Work Environment: A Sociolinguistic Study of Power and Modesty - Nur Alifah (Journal of Psycho Linguistics, 2025)
Differences in gender-based communication patterns in the work environment have been a concern in sociolinguistic studies, given their influence on power dynamics and politeness in professional interactions. The background of this research aims to understand how men and women express power and politeness through language, taking into account the role of social construction and cultural expectations of gender roles in organizations. The purpose of this study is to identify patterns in language use between men and women and understand their implications in an increasingly inclusive work context. This research method uses a qualitative approach with a descriptive method. Data was collected through in-depth interviews and participatory observations on employees in several organizations to explore perceptions, experiences, and communication patterns used in inter-gender interactions. Thematic analysis is used to identify key themes in the use of language related to power and politeness. The results of the study showed that men more often used direct and assertive language to assert authority, while women preferred a persuasive and collaborative communication style. This reflects social expectations of the role of gender in organizational structures. The conclusion of this study shows that these differences in language patterns not only reflect individual preferences, but are also influenced by organizational culture and social norms. The practical implications are that organizations can use these findings to develop more inclusive communication strategies, thereby supporting a more equal and harmonious work environment.